The athlete-as-network and the athlete multiple: potential contributions of actor-network theory to sports coaching research - Kerr, R.; Edwards, S.; Konoval, T. (Sports Coaching Review, 2022)
This article introduces several concepts from Actor-Network Theory (ANT) through problematising the athlete as a heterogeneous entity that is multiply enacted. Through these concepts, we reject the notion that there is only a single underlying biological body as the essence of athletic performance. We instead argue that the athlete is enacted by a network, and that studies of coaching practice must therefore move beyond a restricted focus on the coach-athlete relationship or institutionalised arrangements within a sport. Understanding the athlete as a network reveals the way practices can be more aligned with athlete-centred coaching and adopt a more holistic approach. Through two examples of successful non-institutionalised, athlete-centred arrangements we illustrate how ANT can be used to gain insights into coaching practices that extend current Foucauldian analyses. We conclude that viewing the athlete as multiply enacted highlights differences that could serve as productive spaces for reimagining coaching practice.